Re: Regarding urgency to take post level survey of the building or at least near the escalator opening area in all the floors - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding urgency to take post level survey of the building or at least near the escalator opening area in all the floors of BRACU new campus building.